State sovereignty or ecological sovereignty? : a study of the regulation of acid rain within the European Union - Van der Lugt, Cornelis Theunis (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Phil.) -- University of Stellenbosch, 1998.